Towards ideal window layouts for multi-party, gaze-aware desktop videoconferencing - Junuzovic, Sasa; Inkpen, Kori; Hegde, Rajesh; Zhang, Zhengyou (Graphics Interface 2011, 2011)
In high-end desktop videoconferencing systems, several windows compete for screen space, particularly when users also share an application. Ideally, the layout of these windows should satisfy both (a) layout guidelines for establishing a rich communication channel and (b) user preferences for window layouts. This paper presents an exploration of user preferences and their interplay with previously established window layout guidelines. Based on results from two user studies, we have created five recommendations for user-preferred window layouts in high-end desktop videoconferencing systems. Both designers and end-users can use these recommendations to setup "ideal" layouts, that is, layouts that satisfy both user preferences and existing layout guidelines. For instance, we have developed an application that utilizes the recommendations to guide users towards ideal layouts during a videoconference.